2020
DOI: 10.26434/chemrxiv.12518357.v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Area-Selective Deposition of Ruthenium by Area-Dependent Surface Diffusion

Abstract: <div> <div> <p>Area-selective deposition (ASD) enables the growth of materials on target regions of patterned substrates for applications in fields ranging from microelectronics to catalysis. Selectivity is often achieved through surface modifications aimed at suppressing or promoting the adsorption of precursor molecules. Here we show, instead, that varying the surface composition can enable ASD by affecting surface diffusion rather than adsorption. Ru deposition from (carbonyl)- (alkylcyc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…41 A study by Grillo et al has demonstrated that the surface diffusivity of ALD precursors is higher on surfaces with lower surface energy. 42 Since the ODTS−sapphire SAM shows slightly better crystallinity than ODTS−Si, it is possible that the surface energy of ODTS− sapphire is lower than that of ODTS−Si. Hence, there may be higher precursor surface diffusion on ODTS−sapphire, allowing the physisorbed DEZ precursor to better diffuse into defect sites where nucleation can occur, before they have time to desorb from the ODTS−sapphire surface.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…41 A study by Grillo et al has demonstrated that the surface diffusivity of ALD precursors is higher on surfaces with lower surface energy. 42 Since the ODTS−sapphire SAM shows slightly better crystallinity than ODTS−Si, it is possible that the surface energy of ODTS− sapphire is lower than that of ODTS−Si. Hence, there may be higher precursor surface diffusion on ODTS−sapphire, allowing the physisorbed DEZ precursor to better diffuse into defect sites where nucleation can occur, before they have time to desorb from the ODTS−sapphire surface.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In previous research, the growth of Ru film was inhibited on SiO 2 and annealed indicone surface by the inefficient adsorption mechanisms of the Ru precursor on the SiO 2 surface and absence of the functional groups on the annealed indicone surface. 19,27,42 Adsorption of the T-Rudic precursor is disadvantageous on an OH-terminated Si surface for reaction energy but much more advantageous on an Hterminated Si surface. Another reason for selective metal growth is that aggregation of metals on dielectrics is attributed to differences in surface energies between the dielectric substrate and the metal adlayer.…”
Section: Resultsmentioning
confidence: 99%
“…Another possible process to be considered is the surface diffusion of species as the chemical natures of the PMMA and SiO2 substrates are different. 35,36 We analyze the topography of the patterns to gain further insight into the growth mechanism reported here. ALD processes operating with saturation characteristics typically yield large degrees of uniformity.…”
Section: Resultsmentioning
confidence: 99%
“…Deviations in the form of gradients may indicate diffusion processes 36,37 and explain the increase in GPC.…”
Section: Resultsmentioning
confidence: 99%